STUDI ETNOGRAFI WARGA BOGOR DI TENGAH PANDEMI CORONAVIRUS MENJELANG HARI RAYA IDUL FITRI 1441 H - Vera Yuni Astuti; Mila Yaelasri; Nawiroh Vera (Jurnal Komunikasi dan Budaya, 2022)
Abstract. This study discusses the ethnographic study of Bogor citizens in the midst of the Coronavirus Pandemic ahead of the Eid al-Fitr 1441 H, where the rules of the Large-Scale Social Border (PSBB) are still enforced and Bogor residents carry out activities like normal life as usual. Even though in the midst of the pandemic coronavirus always prioritizes social and physical distance. The effort to maintain distance as an effort to avoid direct contact with sufferers of Coronavirus and avoid the transmission of Coronavirus disease through fluids caused by dropping. The culture of the citizens of Bogor is not only happening in Bogor, but even throughout the world in the lead-up to the Eid al-Fitr, always done by buying new clothes, new shoes and cooking delicious food such as cookies for serving on the living room table and ketupat in the form of opor and rendang during Eid. This has become a common activity for residents to shop at Anyar traditional market in Bogor as an ethnographic study of Bogor residents in this research. With the meeting of Bogor residents in Bogor's Anyar Traditional Market, the distance between residents in interacting during transactions and choosing buying and selling goods was not given enough attention and direct contact was feared for rapid Coronavirus transmission. So that the ethnographic study of the citizens of Bogor in the midst of the Coronavirus pandemic ahead of the Eid al-Fitr was deemed ineffective during the Large-Scale Social Restrictions (PSBB) in Bogor City.